Dynamic sorting and average skyline method for query processing in spatial-temporal data. (26th August 2021) - John, A.; Singh, Shubham Kumar; Adimoolam, M.; Kumar, T. Ananth
With the continuous advancement in mobile computing and development of positioning in devices, querying of moving objects on road networking is an important task in the internet world. As a result of this development, huge amount of data management and query processing plays a vital role in spatial and temporal applications. Large amount of data which is being coupled with different query processing requires efficient indexing. The main problems in spatiotemporal is managing data indexing, updation and query processing. In this work related to the query processing in spatiotemporal data to update different dynamic queries of users. The previous work of query processing will not support to all the end users. The proposed dynamic sorting and average skyline (DSAS) method will support different kinds of query. This method is DSAS and it produces effective query processing to different users at different locations. The skyline query processing technique produces the result for the dominating objects, when compared with the other query processing techniques.